Hubungan Antara Pola Asuh Permisif Dan Kontrol Diri Dengan Perilaku Merokok Elektrik - Cindi Damayanti; Octa Reni Setiawati; Supriyati (Nathiqiyyah, 2026)
The behavior of using electronic cigarettes (vaping) is increasingly prevalent among adolescents and raises concerns as it may affect both health and social development. This study aims to examine the relationship between permissive parenting style and self-control with vaping behavior among adolescents. The research employed a quantitative approach using a survey method. The sample consisted of 85 adolescents aged 18–25 years, selected through accidental sampling. The instruments used included a vaping behavior scale, a permissive parenting scale, and a self-control scale. Data were analyzed using multiple linear regression. The results indicated a significant relationship between permissive parenting and self-control with vaping behavior. Permissive parenting was found to increase the tendency of adolescents to vape, while low self-control further reinforced this behavior. These findings highlight the crucial role of family and self-regulation skills in preventing vaping behavior among adolescents. Keywords: electronic smoking behavior, permissive parenting style, self-control.